Transmission Strategies for Gaussian Relay Networks Obtained from Deterministic Models - Schrammar, N; Skoglund, M (2010 IEEE Global Telecommunications Conference GLOBECOM 2010, 2010)
A constant gap between the deterministic model of a class of a wireless relay network and its Gaussian model counterpart is derived. The method is constructive in the sense that a transmission solution in the deterministic model that obeys certain constraints can directly be translated into a transmission in the Gaussian model. We show that the rate in the Gaussian model is at most a constant gap below the rate in the deterministic model, and we derive an upper bound on this gap.